Managing knowledge in foreign entry strategies: a resource‐based analysis - Meyer, Klaus E.; Wright, Mike; Pruthi, Sarika (Strategic Management Journal, 2009)
International strategies vary in their potential to exploit and augment a firm's resources, especially its knowledge base. Resource‐based analysis suggests clustering the diverse entry modes in terms of their exploitation and augmentation characteristics. We thus introduce a new categorization of entry modes based on their potential to augment the resources of an entrant. We then explore the antecedents of these modes, and advance testable propositions delimiting for which firms and in which circumstances each mode maximizes long‐term value creation. Finally, we outline how our resource‐based framework complements transaction‐cost‐based frameworks.